Pengaruh LDR, NIM Dan ROA terhadap Return Saham (Studi Kasus pada Bank Umum yang Terdaftar di Bursa Efek Indonesia 2014 – 2017) - Any Rustia Dewi (Jurnal Manajemen dan Kewirausahaan, 2019)
This study aims to analyze the effect of Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), and Return on Assets (ROA) on Stock Return. This research population are all banks that listed in Indonesia Stock Exchange (IDX) 2014-2017, with number of sample 13 banks selected by purposive random sampling. The data is analyzed by multiple linear regression analysis. The result of data analysis shows that only Return of Assets (ROA) has a significant effect on stock return.https://doi.org/10.26905/jmdk.v7i1.2983